Surface modification of H-ZSM-5 with organo-disilane compound for propylene production from dimethyl ether - Fujiwara, Masahiro; Mimura, Naoki; Sato, Osamu; Yamaguchi, Aritomo (Microporous and mesoporous materials, 2019)
The efficient modification of zeolites for improving their catalytic properties is a significant subject of microporous materials chemistry. H-ZSM-5 zeolite is a potent catalyst of the production of propylene as an important start material of a variety of chemical products, which is mainly obtained from fossil resources. Recently, the production of propylene using non-fossil carbon resources are desired because of the depletion risk of fossil fuels and global warming problem. Dimethyl ether (DME) conversion to propylene is actively studied using acid catalysts as an alternative synthetic route of propylene. This paper reports the propylene production from DME using H-ZSM-5 catalyst whose surface was modified with an organo-disilane compound, 1,4-bis(hydroxydimethylsilyl)benzene. An H-ZSM-5 catalyst surfacely modified with the disilane compound produced propylene from DME in higher yield than original (non-modified) H-ZSM-5. Air flow treatment at 480 °C effectively regenerated the modified H-ZSM-5 that was deactivated by coke formation during the reaction, and this regenerated catalyst had a nearly equivalent activity of the propylene production to the catalyst before deactivation. The polycyclic aromatic compounds formed from the benzene ring of the disilane compound that covered the exterior surface of H-ZSM-5 controlled the catalytic activity to increase the yield of propylene. [Display omitted] •10% of 1,4‒bis(hydroxydimethylsilyl)benzene was modified on H-ZSM-5 zeolite.•The modified H-ZSM-5 was effective for propylene synthesis from dimethyl ether.•Propylene yield by the modified H-ZSM-5 was more than double of that by H-ZSM-5.•Polycyclic aromatics was formed of the disilane compound on the surface of H-ZSM-5.•Restricting the reaction at exterior surface of H-ZSM-5 improved propylene synthesis.